4H-SiC, ZnSe/ZnS, MAA’s e CCCA’s: propriedades de transporte, eletrônicas, vibracionais e óticas - Maia Júnior, Francisco Franciné (2005)
Four different themes are approached in this work: electronic transport in bulk semiconductors, quantum confinement in semiconductor heterostructures, ab initio calculations for organic molecules and the photoluminescence of ceramics made of rice husk ashes. Transport properties in the transient regime of 4H-SiC were studied. It was observed a characteristic drift velocity overshoot with strong anisotropy in its behaviour along both directions parallel and perpendicular to the c crystalline axis. Transport properties for this material were calculated for different temperatures. The quantum confinement in ZnSe/ZnS quantum wells was examined, with emphasis on the excitonic properties (binding and total energy of e − lh, e − so and e − hh excitons) and how they are affected by the existence of graded interfaces, abrupt well relative position, strain effects (two types of pseudomorphic strain and free-standing strain) and the presence of a lattice mismatch induced piezoelectric field in the case of crystal growth along the (111) direction. It was observed that, despite small effects of lattice mismatch strain on the electronic confinement, the excitonic confinement is particularly sensitive to strain. Ab initio calculations were performed for mycosporine-glycine, palytine and 330-asterine. Atomic positions, charge populations, electronic density, Raman and infrared vibrational spectra and HOMO-LUMO states were obtained showing a significant variation with the calculation level. At last, samples of ceramic made of rice husk ashes were prepaired and characterized. Their photoluminescence varied with the granulometry of the ash particles and depends on the chemical treatment used (acid bath before preparation).